Tissue tolerance of diclofenac sodium encapsulated in liposomes after intramuscular administration - Lima, E. M.; Oliveira, Anselmo Gomes de [UNESP] (Marcel Dekker Inc, 2002)
In this work the effect of the encapsulation of diclofenac sodium within liposomes on the reduction of the myotoxicity after intramuscular administration in rats was studied. Diclofenac sodium was encapsulated in small unilamellar liposomes obtained from phosphatidylcholine, cholesterol, and a-tocopherol (40:10:0.04 mM), and administered by intramuscular injection in the quadriceps femoral muscle of male Wistar rats. After a single dose of 0.2 mg diclofenac formulations the local tissue damage was assessed by plasma creatine kinase (CPK) activity and histological analysis. It was demonstrated that formulations containing free diclofenac produced a higher increase in CPK activity, while those encapsulated in liposomes exhibited CPK activity similar to the control groups. Histopathological analysis of local muscle tissue performed on the third and seventh days following the injection showed intense cellular damage when free drug solution was used, while encapsulation in liposome protected the tissue against the local tissue inflammation.
Keywords: creatine kinase; diclofenac sodium; liposomes; myotoxicity